Keanekaragaman Jenis Bambu di Gunung Ciremai Jawa Barat - Tri Cahyanto; Dhyni Arigustin; Muhammad Efendi (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Mountain Ciremai as in situ conservation, reserve species of bamboo were used for variously of daily needs to handy craft. As the land changes and the increasing a need for bamboo by society, the existence of natural bamboo threatened that an inventory of natural bamboo species needs to be done. This study aims to list the species diversity and abundance of bamboo in Mountain of Ciremai West Java. Sampling is done using qualitative descriptive method which includes exploration, sampling, morphological observation and identification of the type of bamboo and measurement of environmental factors. Data obtained were then analyzed using the Shannon-Wiener diversity index to find out the diversity index species of bamboo in the area Mountain of Ciremai West Java. Based on data collection in the field, found 10 bamboo species namely G. apus J.A & J. H. (shultes) Kurz, S. Silicatum Widjaja, G. pseudoarundnacea (Stard) Widjaja, B. Lako Widjaja, B. blumeana J. A & J. H, S.Brachyladum Kurz, G. AtterHassk. Kurz, D. asper (Schult) Backer ex Heyne, D. aspervar. Thai, B. vulgaris Schard. ex J.C. The type most often found is G. apus J.A & J. H. (Shcultes) Kurz, while the highest abundance was found in D. asper (Schult) Backer ex Heyne 2,500 clump. Based on the calculation of diversity indices in the area Mountain of Ciremai Kuningan relatively low level H '= 0.902164 where H' <1.5. S.brachyladum is belongs to rare species.